(untitled) (Bangladesh Journal of Agricultural Research, 2010)
The present study is an attempt to assess the existing agronomic practices of hybrid maize cultivation, its profitability, constraints, and factors affecting hybrid maize production. The majority of the total farmers sowed seeds during the first week of December. The average seed rate was found to be 20.94 kg per hectare. About 16 varieties were found to cultivate by farmers, of which majority farmers used NK-40 followed by Pacific-II. All kinds of fertilizer used by the farmers were below the optimum level of recommendation. About 33 and 28 percent of the total variable cost was for human labour and chemical fertilizer, respectively. The average yield of hybrid maize was found higher than the national average. The average gross margin was observed to be Tk. 28456 on total variable cost basis. The cost per kilogram of maize cultivation was Tk. 4.12 and return from one kilogram of maize production was Tk. 7.80. It is found that the coefficient of human labour, land preparation, irrigation, urea and borax have significantly impact on gross return. Timely non-availability of seeds, high price of fertilizer, and low price of yield were the major problems for hybrid maize production. Farmers cultivated hybrid maize because of higher yield, higher income, and easy growing. Keywords: Gross return; gross margin; profitability. DOI: 10.3329/bjar.v35i1.5869 Bangladesh J. Agril. Res. 35(1) : 83-93, March 2010